2020
DOI: 10.3389/fgene.2020.00429
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a 13-Gene Signature for Prognosis Prediction in Medulloblastoma

Abstract: Background: Recent studies have identified several molecular subgroups of medulloblastoma associated with distinct clinical outcomes; however, no robust gene signature has been established for prognosis prediction. Our objective was to construct a robust gene signature-based model to predict the prognosis of patients with medulloblastoma. Methods: Expression data of medulloblastomas were acquired from the Gene Expression Omnibus (GSE85217, n = 763; GSE37418, n = 76). To identify genes associated with overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 131 publications
(142 reference statements)
1
1
2
Order By: Relevance
“…This suggests that these TME scores are speci c to different cancers. Wang et al analyzed the TME scores of MB data in the GSE85217 dataset and found that the SHH subgroup had the highest tumor immune and stromal scores [15]. However, in our study, Group3 had the highest immune and stromal scores.…”
Section: Discussioncontrasting
confidence: 68%
“…This suggests that these TME scores are speci c to different cancers. Wang et al analyzed the TME scores of MB data in the GSE85217 dataset and found that the SHH subgroup had the highest tumor immune and stromal scores [15]. However, in our study, Group3 had the highest immune and stromal scores.…”
Section: Discussioncontrasting
confidence: 68%
“…Specific to Group 4, we observed CACNA1A (Calcium Voltage-gated Channel Subunit Alpha1 A), in 21 GERs and was identified in systems biology analysis of Group 4 MBs as a novel therapeutic target [29]. Another recent study profiled the immune repertoire of MBs and found high expression of CACNA1A in Group 4 MB plasma cells [30]. KHDRBS2 was present in 19 GERs and over-expressed in Group 4 tumors and was previously reported as a subgroup-specific gene [31].…”
Section: Studysupporting
confidence: 62%
“…This implies score speci city across cancers. Wang et al analyzed TME scores of MB data in the GSE85217 dataset, nding the SHH subgroup had the highest tumor immune and stromal scores (Li et al, 2020). However, Group3 exhibited the highest immune and stromal scores in our study.…”
Section: Discussioncontrasting
confidence: 47%